Facies Analysis From Kikim Formation in Garba Mountain, South Palembang Subbasin - Daryono, Sapto Kis; Afrilita, Afrilita; Idarwati, Idarwati (Jurnal Ilmiah MTG, 2023)
The Kikim Formation, especially the Cawang Member, has an important role in the formation and stratigraphic evolution of Paleogene age sedimentary rocks in the South Sumatra Basin because of their presence as pre-rift deposits. These deposits occurred before or simultaneously with the basin's formation. The results of research regarding facies analysis and interpretation of the depositional environment of the Kikim Formation located in the Garba Mountains will provide an explanation and description of the history of the formation and stratigraphic evolution of Paleogene age sedimentary rocks in the South Sumatra Basin as reflected in their lithological and facies characteristics. Facies analysis was conducted on the stratigraphic cross-section of the conglomerate deposit and sandstone deposit 1. The conglomerate deposit and sandstone deposit had thicknesses of ± 158.82 m and ± 177.50 m, respectively, on the Bumi Agung and Batu Belang measurement lines, South Ogan Komering Ulu area, Sumatra South. Facies analysis leads to the division of facies according to Miall (1978), namely eight lithofacies, namely Gravel matrix supported massive (Gmm), matrix supported Gravel (Gmg), massive Gravel (Gm), massive Sandstone (Sm), horizontally bedded Sandstones (Sh), low angel cross-bedding Sand (SI), Carbonaceous mud (C), massive Fine sandstone silt mud (Fm), Massive siltstones, and mudstones (Fsm). The facies associations obtained were Gravel Bars (GB), Sandy Bedforms (SB), channel (CH), and Overbank fine (FF). It showed that the depositional environment was a fluvial environment, and it was found that the type of river in the research area in the Kikim Formation was a braided river with Gravel braided rivers with sedimentary gravity flows model.